The Impact of Remote Work on Faculty Members’ Creativity; the Serial Mediating Role of Work-Life Balance and Psychological Well-Being - Abualbasal , Abdelraheem; Issa, Reem; Alfayoumi, Dania; Azzouqa, Seba; Tawabini, Nisreen (Journal of Ecohumanism, 2024)
Purpose –The current study aims to thoroughly investigate the relationship between the implementation of remote work and the creativity of faculty members, while also exploring the serially mediating role of work-life balance and psychological well-being within this relationship. Design/methodology/approach –The quantitative data approach of conducting an online survey was utilized, and the survey was distributed via emails and social media platforms. Through convenience sampling there were a total of 378 participants consisting of faculty members working in Jordan. The IBM SPSS Statistics software (version 29) was used to analyze and process the collected data. In, to test the hypothesized directed relationships and facilitate the conduction of the mediation and serial mediation analyses, Hayse Process 4.1 (model 6) was also utilized. Findings – The study concluded that both work-life balance and psychological well-being have mediating roles in the relationship between remote work and creativity. Additionally, work-life balance and psychological well-being serially mediate the relationship between remote work and creativity. Originality/value –The current study contributes to the literature by investigating both the direct and indirect impacts of remote work on the creativity of faculty members, addressing the immature link and limited research on this relationship, as well as the lack of focus on the higher education sector.